Fuzzy decision by opinion score method (FDOSM):design and development of new multi criteria decision making method - Salih, Mahmood Maher (Tanjong Malim, 2019)
Fuzzy decision by opinion score method (FDOSM):design and development of new multi criteria decision making method by Salih, Mahmood Maher